The Translation Techniques of Anger Expressive Utterances in The Novel The Hate U Give (2017) by Angie Thomas - Meisha Rahmania; Havid Ardi (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
This research was conducted to analyze the translation techniques of anger-expressive utterances found in the Novel The Hate U Give by Angie Thomas, translated into Indonesia. The purpose of the research was to study anger expressions and classify the translation techniques of anger used by the translator in The Hate U Give Novel and its translation. The data were gathered from reading the novel. There are 182 utterances that fall into the category of